Motor potentials of bulbocavernosus muscle after transcranial and lumbar magnetic stimulation: comparative study with bulbocavernosus reflex and pudendal evoked potentials. - Ghezzi, A (1991)
Motor potentials of the bulbocavernosus muscle were recorded in 17 healthy subjects after transcranial and lumbar magnetic stimulation. The latencies (SD) were respectively: 22.9 (1.8) and 5.9 (0.4) ms. The central conduction time was 17.0 (2.5) ms. The bulbocavernosus reflex presented an onset at 34.5 (3.3) ms and a negative peak at 43.1 (3.9) ms. The cortical pudendal evoked potential was W shaped: the first peak had a latency of 35.4 (2.8) ms. The concurrent recording of motor potentials, bulbocavernosus reflex, pudendal evoked potentials gives a measure of peripheral and central, afferent and efferent neurological pathways related to pudendal nerve function.